The Existence of Political Costs as a Condition for Advancement in Election Contestation in Indonesia - Putra, Zulfikar; Wajdi, Farid (CV. Rayyan Dwi Bharata, 2025)
Whenever discussing political events, the thing that does not escape discussion is the cost or cost that must be incurred for political financing. It cannot be denied that every political activity carried out by individuals and political parties cannot be avoided by the political costs accompanying it. The purpose of this research is to find out the existence of political dowries issued in every election contestation in Indonesia, the methods used to win in election contestation, to find out the chances of winning for election contestants with the ability to spend a lot of money and little money. The method used in this research is library research, where secondary data sources are taken from a collection of articles, books, and other readings related to the research. The result of the research is that every contestation in the election cannot be avoided by spending money, because the consequences of every competition (competition) to win the sympathy and support of voters (the people) need the cost of campaign props (stickers, business cards, billboards, etc.), the cost of transportation fuel used to visit voters, the cost of data pulses and so on. This research concludes that it is a necessity for every person who will advance to compete either as a Legislative Candidate, Candidate for Regent / Mayor or Governor and Presidential Candidate, there is financing that must be incurred in the success of his candidacy